The Qur'anic Education Strategies for the Indonesian Context: An investigation of the Halaqah of the Qur’an in Mecca and Medina - Hidayati, Tri Wahyu; Gufron, M. (International Journal on Advanced Science, Education, and Religion, 2024)
This paper aims to provide a comprehensive perspective on strategies for promoting Qur'anic education in the Indonesian context. The study examines the halaqah of the Quran in Mecca and Medina within the strategic framework of the Qur'anic teaching-learning process. The study begins by highlighting the miserable fact that the current young Muslim generation in Indonesia lacks an interest in the Qur'an. This condition leads not only to the absence of Qur'anic spiritual values in their lives but also to the loss of the tradition of studying the Quran in Muslim societies. This research employs a combined research model that involves a literature review and field research. This study concludes by identifying three key strategies for improving Qur'anic education in Indonesia. First, by using a dialogical approach, the tradition of the halaqah of the Qur'an can be employed as a model for developing the tradition of learning the Qur'an in Indonesia. Second, to develop Qur'anic education in Indonesia, three fundamental components are critical, namely: developing learning spirit and motivation; extending time flexibility and learning innovation; and achieving external support. Third, the learning steps are addressed systematically as part of the integrated contextual learning approach. It covers facilitating a collaborative, supportive, and interactive learning environment. By integrating these elements, it is hoped that Qur'anic education in Indonesia can develop properly and reach a high level of productivity.